Gradient-based energy balancing and current control for alternate arm converters - Wickramasinghe, Harith R. (2020)
The alternate arm converter (AAC) is an emerging fault-tolerant multilevel converter topology from the same family of multilevel converters as the modular multilevel converter (MMC). Due to the alternate operation of the converter arms, energy balancing in the AAC is not continuous, but restricted to small time intervals. This paper develops a gradient-based current control and energy-balancing method for the AAC. The proposed strategy enforces the dynamic limits on the redundant submodules (SMs) during the overlap period and allocates effectively the maximum available number of redundant SMs to control the circulating current. The choice of the gradient as the circulating current control parameter improves the energy regulation capability of the AAC, and the enforcement of dynamic limitations avoids distortions of the output voltage. Results from an AAC-based HVDC converter model derived from the CIGRE benchmark MMC system demonstrate that the proposed strategy delivers improved energy control and balancing with good harmonic performance compared to existing current control methods for the AAC while also maintaining zero-current switching of the director switches of the AAC arms.